The misconception of the option value of deposit insurance and the efficacy of non-risk-based capital requirements in the literature on bank capital regulation - Fegatelli, Paolo (Journal of Financial Stability, 2010)
This study shows how the misconception of the option value of deposit insurance by Merton (1977) and its later misuse by Keeley and Furlong (1990), among others, have led some literature supporting the adoption of binding non-risk-based capital requirements to derive incorrect conclusions about their efficacy. This study further shows that what Merton defines as the option value of deposit insurance is actually a component of a bank's limited liability option under a third-party deposit guarantee. As such, it is already included in the value of the bank's equity capital, and the flawed definition makes the Keeley–Furlong model internally incoherent.